Innovative applications of advanced nanomaterials in cerebrovascular imaging - Na, Li; Song, Xiaofu; Luo, Ping; Su, Jingqi; Yao, Zhicheng (Frontiers in Bioengineering and Biotechnology, 2025)
Cerebrovascular imaging is essential for the diagnosis, treatment, and prognosis of cerebrovascular disease, including stroke, aneurysms, and vascular malformations. Conventional imaging techniques such as MRI, CT, DSA and ultrasound have their own strengths and limitations, particularly in terms of resolution, contrast and safety. Recent advances in nanotechnology offer new opportunities for improved cerebrovascular imaging. Nanomaterials, including metallic nanoparticles, magnetic nanoparticles, quantum dots, carbon-based nanomaterials, and polymer nanoparticles, show great potential due to their unique physical, chemical, and biological properties. This review summarizes recent advances in advanced nanomaterials for cerebrovascular imaging and their applications in various imaging techniques, and discusses challenges and future research directions. The aim is to provide valuable insights for researchers to facilitate the development and clinical application of these innovative nanomaterials in cerebrovascular imaging.